1997
DOI: 10.1042/bj3280745
|View full text |Cite
|
Sign up to set email alerts
|

Nascent very-low-density lipoprotein triacylglycerol hydrolysis by lipoprotein lipase is inhibited by apolipoprotein E in a dose-dependent manner

Abstract: In the present study it was investigated whether apolipoprotein (apoE) can inhibit the lipoprotein lipase (LPL)-mediated hydrolysis of very-low-density-lipoprotein (VLDL) triacylglycerols (TAGs). Previous studies have suggested such an inhibitory role for apoE by using as a substrate for LPL either plasma VLDL or artificial TAG emulsions. To mimic the in vivo situation more fully, we decided to investigate the effect of apoE on the LPL-mediated TAG hydrolysis by using VLDL from apoE-deficient mice that had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 31 publications
6
42
1
Order By: Relevance
“…This appears to be a major reason for the TG increase because there is no difference in TG secretion rates between the Apoe 2/2 ·Apobec Ϫ/Ϫ and Apoe 2/2 mice. Increases in apoE plasma levels can have a dose dependent inhibition on LpL activity (25)(26)(27)(28). However, we found the Apoe 2/2 · Apobec Ϫ/Ϫ mice have similar amounts of plasma and VLDL apoE-2 as compared with the Apoe 2/2 mice, which excludes the levels of apoE-2 as a cause for decrease in VLDL lipolysis.…”
Section: Discussioncontrasting
confidence: 52%
“…This appears to be a major reason for the TG increase because there is no difference in TG secretion rates between the Apoe 2/2 ·Apobec Ϫ/Ϫ and Apoe 2/2 mice. Increases in apoE plasma levels can have a dose dependent inhibition on LpL activity (25)(26)(27)(28). However, we found the Apoe 2/2 · Apobec Ϫ/Ϫ mice have similar amounts of plasma and VLDL apoE-2 as compared with the Apoe 2/2 mice, which excludes the levels of apoE-2 as a cause for decrease in VLDL lipolysis.…”
Section: Discussioncontrasting
confidence: 52%
“…24 -26 However, this negative effect on triglyceride lipolysis may be partly apoE isotype independent, because wild-type apoE3 can also decrease the efficiency of triglyceride lipolysis when present at high levels on the VLDL. 23,[27][28][29][30] On the basis of our experiments, we cannot distinguish quantitative effects from qualitative effects of apoE2 and apoE3-Leiden on the efficiency of triglyceride lipolysis. It has recently been described that increased levels of mouse apoE in the serum of ApoeϪ/Ϫ.LdlrϪ/Ϫ mice do not result in hypertriglyceridemia.…”
Section: Discussionmentioning
confidence: 90%
“…This is likely caused by a delayed lipoprotein clearance that is due to the presence of APOE3Leiden in high concentrations and a consequently decreased hydrolysis of VLDL-TG. Jong et al 38 have shown that high concentrations of apoE inhibit lipolysis, probably by steric hindrance of lipoprotein binding to heparan sulfate proteoglycans. Reduced lipolysis of TG-rich particles in APOE3Leiden transgenic mice in the presence of mouse apoe 18 is probably due to the lower binding affinity of APOE3Leiden to heparan sulfate proteoglycans.…”
Section: Discussionmentioning
confidence: 99%